Offshore bet: The benefits of capital mobility - Diego Zuluaga (Institute of Economic Affairs (IEA), 2018)
Offshore financial centres (OFCs) are alleged to be hotbeds of tax evasion. Their role in facilitating individual and corporate tax planning, which is entirely legal but politically controversial, has also come under the spotlight. However, OFCs play an important economic function. By mitigating instances of double and triple taxation, offshore centres raise aggregate investment. Their existence is also associated with better economic outcomes in the countries that surround them. The recent growth in the number and size of OFCs can be explained by three developments: an increase in the stock of investable capital, new investment opportunities outside Western Europe and North America, and the growth of tax and regulatory intervention by governments. As more investment capital is allocated across a diverse range of jurisdictions from investors around the world, the potential for multiple taxation increases. The role of OFCs in eliminating excessive taxation has a positive impact on investment returns which compounds over time. There is no evidence that the rise of OFCs has adversely affected the revenue-raising ability of other countries. For example, corporate tax revenue as a share of all taxes collected has grown slightly in the average OECD country since 1980. Nor is it true that OFCs levy no taxes: their average tax revenue as a share of national income is only six percentage points lower than across the OECD. OFCs do, however, rely on indirect (e.g. consumption) taxes rather than direct (e.g. income) taxes for revenue. Indirect taxes are often less distortionary. The popular account of offshore centres is an outdated caricature that bears little resemblance to how OFCs in fact operate. Undermining their existence would harm investment, economic growth and international capital flows, while the promised benefits from intervention are unlikely to materialise.
Keywords: H26; H21; H11; L51; J11; J18; F22; F38; H26; H21; H11; L51; J11; J18; F22; F38; 330